Clinical effects of COVID-19 vaccines on chronic spontaneous urticaria patients: a study on two Turkish centers - Kartal, Demet; Orujova, Shahzada; Ertaş, Ragıp (Frontiers in Medicine, 2023)
Background The relationship between CSU and vaccines is reported in the literature. The post-vaccine clinical effect of COVİD-19 vaccines on CSU patients is still unclear. we aimed to evaluate clinical effects of COVID-19 Vaccines on CSU patients. Materials and methods CSU patients under treatment and follow-up in our outpatient clinic were evaluated retrospectively. To determine disease activity the urticaria activity score over seven days (UAS7) was used. The details of demographic information, CSU treatment, history of COVID-19 infection and exacerbation of urticaria during infection, COVID-19 vaccinations, type of vaccine, side effect reaction time after vaccination, hospital admission requirement were also assessed. Results Total of 190 patients with a mean age of The mean age of patients was 41,7±14,0 years (range = 18–72) were enrooled. The patient sample consisted of 50 males and 140 females (male/female ratio 1:2.8). 181 (CoronaVac 77, Pfizer-BioNTech 104) patients were vaccinated. Urticarial exacerbation was occurred in 25 patients. The median UAS value was 5 before vaccination, it was 12 in patients with post-vaccine urticaria. Two patients had angioedema and one patient had anaphylaxis after vaccinated with Pfizer-BioNTech. Conclusion COVID-19 vaccination in the CSU can be considered safe. Cases with urticarial exacerbation appear to be transient and can be managed by antihistamine and/or systemic steroid therapies. More extensive studies are needed for the relationship with CSU and post-coronavirus vaccination anaphylaxy.